Researches on Veterinary Medicine in Turkey: III. Views and Expectations on Job Opportunities and Cross-sectoral Orientations - Ozen, Abdullah; Dogan, Ozlem; Gul, Raziye Tamay Basagac; Ozkul, Turel; Yuksel, Erhan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2012)
Although some points of job opportunities and employment areas of veterinarians were mentioned in various editions in Turkey, countrywide study was not determined. The present study was undertaken to determine the permanent employment status, changing job opportunities and cross-sectoral orientations of veterinarians and to evaluate the views and expectations regarding to sectors for near future and the year 2023. For this aim, a questionnaire was applied to totally 771 veterinarians, from public workers (398) and private sector workers (377). According to data analysis, it was determined that public sector employees expect more to found a permanent job when compared with private sector employees but change their job less than others. Although private sector seems to be more advantageous in terms of job opportunities the transition from private sector to public sector was found to be higher rates in today's conditions. The particular fields expected to have the highest improvement potential were 'food quality and security;'organic agriculture-animal husbandry','herd health',public health' and 'companion animal sector' in near future and 2023. In conclusion, it can be said that public space are more preferable than the other work areas in veterinary medicine in Turkey and the opinions of participants about the areas which will gain the importance in next future and 2023 year point to One medicine one health concept awareness.
Türkiye'de veteriner hekimli?i üzerine araştırmalar: III. iş fırsatları ve sektörel yönelimlere i?lişkin görüş ve beklentiler
Keywords: Job opportunities; Cross-sectoral orientations; Veterinary medicine